2002
DOI: 10.1017/s0950268802007252
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Actinobacillus pleuropneumoniae in pigs is characterized by variation in infectivity

Abstract: SUMMARYTen transmission trials with Actinobacillus pleuropneumoniae were carried out. The observed transmission was highly variable, which was surprising since the design of the trials was very similar. We investigated whether the variable transmission could be explained by variation in infectivity of A. pleuropneumoniae infected pigs. We looked for measurable characteristics, which could be indicative for infectious pigs or for the level of infectivity. The characteristic that appeared to be most indicative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…Experimentally, it has been shown that transmission of A. pleuropneumoniae from subclinically infected pigs by direct contact occurs with a rate ˇ of about 0.1 day −1 , meaning that every infectious pigs can infect on average 0.1 susceptible piglets per day (Velthuis et al, 2002(Velthuis et al, , 2003. Transmission by indirect contact, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it has been shown that transmission of A. pleuropneumoniae from subclinically infected pigs by direct contact occurs with a rate ˇ of about 0.1 day −1 , meaning that every infectious pigs can infect on average 0.1 susceptible piglets per day (Velthuis et al, 2002(Velthuis et al, , 2003. Transmission by indirect contact, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the mean time to absorption and its variance are expressed in terms of R ! by equations (7) and (8). Second, the results show that the FS algorithm underestimates R !…”
Section: Discussionmentioning
confidence: 81%
“…For instance, Velthuis et al [8] studied the transmission of Actinobacillus pleuropneumoniae among pigs by means of a transmission experiment. The excretion pattern of the bacterium in tonsillar swabs and nasal swabs was highly variable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations